High Level Resistance against Rhizomania Disease by Simultaneously Integrating Two Distinct Defense Mechanisms - Pavli, Ourania I. (Public Library of Science, 2012)
With the aim of achieving durable resistance against rhizomania disease of sugar beet, the employment of different sources of resistance to Beet necrotic yellow vein virus was pursued. To this purpose, Nicotiana benthamiana transgenic plants that simultaneously produce dsRNA originating from a conserved region of the BNYVV replicase gene and the HrpZ(Psph) protein in a secreted form (SP/HrpZ(Psph)) were produced. The integration and expression of both transgenes as well as proper production of the harpin protein were verified in all primary transformants and selfed progeny (T1, T2). Transgenic resistance was assessed by BNYVV-challenge inoculation on T2 progeny by scoring disease symptoms and DAS-ELISA at 20 and 30 dpi. Transgenic lines possessing single transformation events for both transgenes as well as wild type plants were included in inoculation experiments. Transgenic plants were highly resistant to virus infection, whereas in some cases immunity was achieved. In all cases, the resistant phenotype of transgenic plants carrying both transgenes was superior in comparison with the ones carrying a single transgene. Collectively, our findings demonstrate, for a first time, that the combination of two entirely different resistance mechanisms provide high level resistance or even immunity against the virus. Such a novel approach is anticipated to prevent a rapid virus adaptation that could potentially lead to the emergence of isolates with resistance breaking properties.